Technology moral sense: Development, reliability, and validity of the TMS scale in Chinese version - Wu, Wen; Huang, Xiuqing; Li, Xinyu (Frontiers in Psychology, 2023)
The aggregation of intelligent technologies such as big data, algorithms, and biometrics poses new moral risks to humanity and has raised awareness of technology ethics. Based on the research on moral issues in the fields of ethics and psychology, we built the concept of technology moral sense（TMS）by investigating three dimensions—technology moral consensus, cognition, and emotion. We focused on the field of intelligent surveillance technology, adopted a scale, and conducted a questionnaire survey with more than 1000 respondents. We used exploratory and confirmatory factor analysis to test two different samples. First, by combining item analysis and Cronbach's alpha coefficient, we established that all three dimensions are reliable. Our results indicated a Cronbach's alpha coefficient of 0.944, 0.891 and 0.938 for technology moral consensus, emotion, and cognition. Second, exploratory factor analysis verified that there were three factors, the eigenvalues were all greater than one, and the cumulative variance explanation rate was 74.953%, and the factor loading coefficient of the 18 items are greater than 0.5. Finally, we used confirmatory factor analysis to test the fit of the model. The test shows that RMSEA = 0.078, CFI and TLI are greater than 0.9, which indicating the fit was suitable and the construct validity was good. The results support the reliability and validity of the Technology Moral Sense (TMS) scale.